A thin, wideband transmissive cross polarization converter - Negin Pouyanfar; Javad Nourinia; Changiz Ghobadi; Vahid Nayyeri (Scientific Reports)
Abstract This study presents a very thin wideband linear polarization converter in transmission mode with near-unity conversion efficiency. The suggested converter consists of a periodic array on a single-layer substrate, two metallic layers and six vias. Metallic vias connect the upper and lower layers of the construction. The radiated electromagnetic wave with linear polarization can be transformed into its orthogonal component in the transmission mode by the proposed converter. The suggested polarization converter operates well in the 9.53–13.35 GHz frequency band (36%). Additionally, The structure provides a larger than 90% Polarization Conversion Ratio (PCR) through the frequency range of 8.89–14.21 GHz. The conversion mechanism has been explained and confirmed through both surface current distribution, electric charge distribution and experimental tests. Over the whole frequency range, there is good agreement between the simulated and measured results.